Strengths-Based Multicultural Counseling (SBMC) Model: An Approach for Counselors and Guidance and Counseling Teachers in the 21st Century - Rahmawati, Novi Rosita; Utomo, Prio (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The diversity among students serves as a valuable potential for fostering dynamic interactions and personal growth. To harness this potential, every student must cultivate multicultural awareness, which does not develop automatically but requires intentional efforts from an early stage. This article highlights the critical importance of strengths-based multicultural counseling and its relevance in the 21st century. The study utilizes a literature review as a methodological approach to emphasize the significance of strengths-based multicultural counseling, focusing on the opportunities and challenges faced by counselors and guidance teachers in contemporary contexts. Findings from the study reveal that strengths-based multicultural counseling is recognized as a